2003
DOI: 10.4269/ajtmh.2003.68.480
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Evidence of Infection With Ehrlichiae and Spotted Fever Group Rickettsiae Among Residents of Gag Island, Indonesia

Abstract: The causative agents of scrub and murine typhus are considered endemic to Indonesia. However, the presence of spotted fever group rickettsiae and ehrlichiae have not been previously described in this country. During an investigation of arthropod-borne diseases on Gag Island, located northwest of the island of New Guinea in eastern Indonesia, the prevalence of antibody to the etiologic agents of monocytic ehrlichiosis, spotted fever rickettsiosis, and scrub and murine typhus were determined. Analysis of 55 bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 29 publications
(53 reference statements)
1
12
1
Order By: Relevance
“…Thus, the high prevalence of murine typhus reported in Indonesia likely also includes fleaborne spotted fever. In addition, previously demonstrated serologic evidence of spotted fever group rickettsiae infection among residents of Gag Island, in eastern Indonesia (15), could have been due to R. felis. On the basis of data presented here and of recent reports of R. felis in other countries in Asia (2)(3)(4)(5)8,9), healthcare providers in Indonesia should be alerted to the possibility of fleaborne spotted fever among their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the high prevalence of murine typhus reported in Indonesia likely also includes fleaborne spotted fever. In addition, previously demonstrated serologic evidence of spotted fever group rickettsiae infection among residents of Gag Island, in eastern Indonesia (15), could have been due to R. felis. On the basis of data presented here and of recent reports of R. felis in other countries in Asia (2)(3)(4)(5)8,9), healthcare providers in Indonesia should be alerted to the possibility of fleaborne spotted fever among their patients.…”
Section: Discussionmentioning
confidence: 99%
“…47,52,61 Outbreaks have also been reported mainly in rural agricultural areas, 29 but cases have been seen in urban centers of Southeast Asia. 22,30,63 Unlike murine typhus, seasonal variations can be found with scrub typhus; incidence increases towards the end of the rainy season and the beginning of winter months (July-November) in Southeast Asia. 27,28 Most scrub typhus cases are mild and characterized by acute onset fever, myalgia, generalized lymphadenopathy, maculopapular rash, and splenomegaly.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…felis, the agent that causes ßea-borne spotted fever, has been shown to infect ßeas of peridomestic rodents and ßeas other than the primary vector, Ctenocephalides felis, in Java, Indonesia (Azad et al 1997, Parola et al 1998, Richards et al 2003, Jiang et al 2006. R. felis was Þrst shown to infect Indonesian X. cheopis collected in Java in 1994 (Jiang et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Scrub typhus (Orientia tsutsugamushi) has been recognized in Indonesia since World War II, where it was a major nonbattle injury for military forces (GrifÞths 1945). Richards et al (2003) found evidence of spotted fever group (SFG) rickettsiae (SFGR) infection in human residents of Gag Island, Indonesia, located northwest of the island of Irian Jaya in Eastern Indonesia.…”
mentioning
confidence: 98%